The influence of experimental gestational diabetes on expression of Aire mRNA and character of differentiation of Foxp3+ - cells in mesenteric lymph nodes in the offspring. - Kamyshny, A. M.; Prozorova, T. M.; Kamyshna, V. A. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Formation of immunological tolerance to self-antigens is an important mechanism that prevents development of the autoimmune diseases. Objective. With the help of molecular genetic and immunofluorescence techniques to investigate the effects of experimental gestational diabetes on the level of mRNA expression of autoimmune regulator Aire and differentiation features of Foxp3+ cells in mesenteric lymph nodes in the offspring of Wistar rats. Methods. To determine the level of Аire mRNA RT-PCR was performed in real-time by thermocycler CFX96™ Real-Time PCR Detection Systems («Bio-RadLaboratories, Inc», USA). The relative level of gene expression were studied with rat reference genes GAPDH by the method ΔΔCt. Statistical analysis were conducted using available software «Bio-Rad СFX Manager 3.1» (Bio-Rad, USA). The immunopositive Foxp3+-lymphocytes were determined using an indirect immunofluorescence technique with using a monoclonal rat antibody. Results. The offspring of experimental gestational diabetes rats showed the reduction of autoimmune regulator Aire mRNA in 2,3-8,1 times (p <0,05) in mesenteric lymph node cells compared to control animals. The observed decrease in the transcriptional activity of Aire is accompanied by reduction in the number of regulatory Foxp3+ lymphocytes in mesenteric lymph node in the offspring of rats with experimental gestational diabetes, as well as reduction of concentration of the transcription factor Foxp3 in lymphocytes of cortical plateau. Conclusion. The revealed changes evidence the abuse of formation of peripheral immunological tolerance and can trigger the development of autoimmune disease in the offspring of mothers with experimental gestational diabetes.